Definisi Ketidakstabilan Mikrosatelit pada Kanker: apa yang harus diketahui - Abdallah, Mays Talib; Al-Shakarchi, Ola E; Hussein, Asmaa A; Abdulmuttaleb, Mohammed Essam; Alsammarraie, Ahmed Zuhair; Aziz, Ismail H; Dawood, Noor Jabbar; Kadhom, Mohammed (Fakultas Kedokteran Universitas Trisakti, 2025)
Microsatellite instability (MSI) is the result of flaws in the DNA mismatch repair (MMR) system that cause insertions or deletions in repetitive DNA sequences known as microsatellites. A hallmark of Lynch syndrome, MSI affects 8–22% of sporadic cancers, including colorectal, gastric, and endometrial carcinomas. Clinically, MSI predicts immune checkpoint inhibitor (ICI) treatment; MSI-high (MSI-H) tumors show better response rates than others. Treatment results, prognosis, and chemotherapy sensitivity among MSI-H patients show notable variation, though. Next-generation sequencing (NGS), which concurrently evaluates tumor mutational burden (TMB) and actionable mutations, immunohistochemistry (IHC) for MMR protein loss, and PCR-based fragment analysis, defines MSI detection. Although IHC is affordable for Lynch screening, NGS provides more extensive genomic profiling. Though they need verification, new technologies such as artificial intelligence-based histomorphological analysis and single-molecule molecular inversion probes (smMIPs) are encouraging. The prognostic effect of MSI differs by cancer kind and stage. MSI-H in early-stage colorectal cancer (CRC) is linked to better survival, but less advantage from 5-fluorouracil chemotherapy. Confounding variables like BRAF mutations cloud the prognostic function in metastatic CRC. Apart from CRC, MSI-H forecasts good results in prostate, gastric, and ovarian cancers but a bad prognosis in breast cancer. Emphasizing its dual function as a diagnostic, prognostic, and therapeutic biomarker, this paper combines MSI's molecular mechanisms, detection techniques, and clinical relevance. Among the difficulties are test standardization and immunotherapy response heterogeneity resolution. Future studies should look at liquid biopsies and combination treatments to maximize precision cancer driven by MSI.